Peran Strategis Sosialisasi Dan Pelatihan Dalam Meningkatkan Kepatuhan K3 Radiologi : Studi Kuantitatif Di Instalasi Radiologi Rumah Sakit Type A - Ahmad Hasmi; Ahmad Hariri; Wilda Wahyuni; Agus Rochmat (Jurnal Ners, 2025)
This study aims to analyze the influence of socialization and training on employee compliance with Radiation Occupational Health and Safety (OHS) procedures in the Radiology Unit of Hospital Type A. Utilizing a quantitative approach with an explanatory associative design, data were collected through a closed-ended questionnaire distributed to 50 respondents selected using purposive sampling. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26. The results indicate that both socialization and training have a significant effect on compliance with radiation safety procedures, with significance values of p = 0.001 and p = 0.000, respectively. The training variable (regression coefficient = 0.41) showed a greater impact on compliance compared to socialization (regression coefficient = 0.35). The regression model yielded a coefficient of determination (R²) of 0.481, indicating that 48.1% of the variance in compliance can be explained by the two independent variables. These findings highlight the importance of structured training programs and continuous safety socialization in fostering a strong safety culture within hospital radiology environments.